Multivalvular enterococcal native valve endocarditis: A case report - Debasish Das; Satyapriya Mohanty; Anindya Banerjee; Abhinav Kumar; Pranjit Deb; Jaideep Das Gupta; Shashikant Singh (Heart and Mind, 2024)
We present an extremely rare case of multivalvular endocarditis in an immunocompetent host which is not observed in routine clinical practice. Multivalvular endocarditis is extremely rare to find in today's era due to the widespread use of broad-spectrum antibiotics to treat pyrexia of unknown origin (PUO). Multivalvular involvement is usually encountered in immunocompromised individuals and is most often due to staphylococcal in origin. It is scarce to find our case of a 73-year-old elderly nondiabetic female with PUO who was diagnosed to be having endocarditis of both aortic and mitral valves showing large friable vegetations. In contrast, her urine and blood culture both had grown Enterococcus species. We successfully treated the patient with parenteral ampicillin and gentamycin for eight weeks, which made the patient afebrile and resolved the vegetation.